Unlocking Sustainability in Informal Micro Enterprises: Capital Access in The Fintech Era - Ispriyahadi, Heri; Zaenudin, Zaenudin; Wati, Lela Nurlaela (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study offers a unique exploration of how capital access mediates the impact of financial literacy and fintech peer-to-peer (P2P) lending on the sustainability of micro and small enterprises (MSEs) in traditional markets, utilizing SDG-based indicators. Research Object: This study examines the effects of financial literacy and fintech P2P lending on capital access and sustainability of MSEs in traditional markets. Research Methods: The study employed a quantitative approach, utilizing Structural Equation Modeling analysis, using 232 MSEs in Jakarta. Empirical Results: The findings indicate that financial literacy and fintech P2P lending have a positive impact on both capital access and the sustainability of MSEs. However, capital access did not significantly affect the sustainability of MSE or mediate either factor. Implications: The Financial Services Authority (OJK) must enhance legislation protecting MSEs from fintech risks and promote financial literacy. The OJK must coordinate P2P platforms, cooperatives, and MSE offices. Creating an inclusive fintech ecosystem for traditional market MSEs, with microloans and mentorship, is essential for viable financing. JEL Classification: G21, G53, L26, O16, Q01 How to Cite:Ispriyahadi, H., Zaenudin, Wati, L. N. (2025). Unlocking Sustainability in Informal Micro Enterprises: Capital Access in the Fintech Era. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 467-488. https://doi.org/10.15408/sjie.v14i2.46421.